2018
DOI: 10.3390/d10020048
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Diversity of Plankton in the Epipelagic and Mesopelagic Layers of the Tropical and Equatorial Atlantic Determined with Stable Isotopes

Abstract: Plankton living in the deep ocean either migrate to the surface to feed or feed in situ on other organisms and detritus. Planktonic communities in the upper 800 m of the tropical and equatorial Atlantic were studied using the natural abundance of stable carbon and nitrogen isotopes to identify their food sources and trophic diversity. Seston and zooplankton (>200 µm) samples were collected with Niskin bottles and MOCNESS nets, respectively, in the epipelagic (0-200 m), upper mesopelagic (200-500 m), and lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 59 publications
3
6
0
Order By: Relevance
“…Opportunistic feeding on prey that are scarce (i.e., low plankton biomass) and diverse would cause large variations in the isotopic composition of both prey and consumers, and therefore would produce large isotopic niches. Similar results were found in plankton from deep layers of the Atlantic, where the communities living in tropical, oligotrophic zones showed isotopic niches of large size (Bode and Hernández-León, 2018). From an ecological perspective, it can be suggested that the U-OLIGO-Z, representing a special ecosystem of the South Pacific central gyre, may be less sensitive to a changing environment upon a greater plasticity of species to exploit highly diverse resources.…”
Section: Discussionsupporting
confidence: 69%
“…Opportunistic feeding on prey that are scarce (i.e., low plankton biomass) and diverse would cause large variations in the isotopic composition of both prey and consumers, and therefore would produce large isotopic niches. Similar results were found in plankton from deep layers of the Atlantic, where the communities living in tropical, oligotrophic zones showed isotopic niches of large size (Bode and Hernández-León, 2018). From an ecological perspective, it can be suggested that the U-OLIGO-Z, representing a special ecosystem of the South Pacific central gyre, may be less sensitive to a changing environment upon a greater plasticity of species to exploit highly diverse resources.…”
Section: Discussionsupporting
confidence: 69%
“…The high variability observed in δ 13 C values among blue whales sampled just a few days apart suggests that individuals within the population foraged across a strong gradient in baseline δ 13 C values. Such gradients are often associated with sharp transitions in biogeochemistry, oceanography and productivity across major biogeographic domains [27,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Ratios of nitrogen also varied between provinces, according to the differences found in δ 15 N values of Oncaeidae. Low δ 15 N values could be due to diazotrophy since the atmospheric nitrogen presents δ 15 N = 0‰, and it can be traced through the food web (McClelland et al, 2003;Mompeán et al, 2016a;Bode and Hernández-León, 2018). This process is mediated by specialized prokaryotes -diazotrophs -which thrive in usually nitrate-poor, warm and stratified waters such as the ones of the subtropical and tropical gyres (Falkowski, 1997;Zehr et al, 2003;Capone et al, 2005;Luo et al, 2012) and introduce into the ocean bioavailable nitrogen depleted in δ 15 N (Somes et al, 2010).…”
Section: Discussionmentioning
confidence: 99%